THE MOTHER’S ROLE IN HEALTH CONSCIOUS CONSUMER SOCIALIZATION OF CHILDREN - Szucs, Robert Sandor; Szell, Eniko (European Scientific Journal, ESJ, 2013)
In our research we were searching for a correlation between childhood obesity and the mother’s body shape and lifestyle. Using the Cramer’s V co-efficient, we have examined the relationship between the body shape according to BMI and the one judged by the respondent mothers. The results do not reflect the actuality in Hungary. The Cramer’s V coefficient, which measures the correlation between body shape according to BMI and the judged data of mothers were moderate: 0.519 which means that the respondents were not able to pinpoint their own exact BMI and body shape. Body shape of children supposed by mothers was also not accurate. The same tendency applies in the care of children’s supposed body shape judged by their mothers. According to our research, we can state that body type of mothers exercises influence on body shape of children. Level of influence depends on the age of children (3.6 – 8.5%).